2002
DOI: 10.1155/2002/745764
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis and Epstein-Barr Virus

Abstract: OBJECTIVE:To evaluate the epidemiological evidence for an etiological role of Epstein-Barr virus in multiple sclerosis (MS). DATA SOURCES: MEDLINE and Cochrane Library searches of the medical literature identified 24 studies. DATA EXTRACTION: Studies were categorized as seroepidemiological, case-control or historical cohort, and were then classified within each group according to methodological rigour using criteria derived from published guidelines for the epidemiological study of MS. DATA SYNTHESIS: There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Ratings of methodological rigor were applied using criteria derived from published guidelines for the epidemiological study of MS (26; Appendix 1). These criteria have been used previously (27, 28), but have not yet been assessed for reliability. They were designed to facilitate the comparison of different studies by providing a qualitative impression of the soundness of the study design and methods.…”
Section: Methodsmentioning
confidence: 99%
“…Ratings of methodological rigor were applied using criteria derived from published guidelines for the epidemiological study of MS (26; Appendix 1). These criteria have been used previously (27, 28), but have not yet been assessed for reliability. They were designed to facilitate the comparison of different studies by providing a qualitative impression of the soundness of the study design and methods.…”
Section: Methodsmentioning
confidence: 99%
“…The work of Holmøy [14] concluded that vitamin D deficiency and EBV infection are both very common population-wide events, and could be involved in MS pathogenesis. Finally, other authors [5,15] in two well-designed cohort studies found increased relative risks of MS in subjects with IM, but the results from other studies were unconvincing [16].…”
Section: Introductionmentioning
confidence: 97%
“…Viral infections have long been an area of interest as precipitating factors of MS. Studies have evaluated an association with childhood viral infections including measles, mumps, rubella and varicella, but data have failed to demonstrate a link to MS development [10]. Epstein-Barr virus (EBV) has gained the most interest as a potential environmental factor for MS. An increased EBV antibody seroprevalence has been found to occur in MS patients compared to controls [11,12]. While current evidence is not sufficiently robust to confirm an increased risk of developing MS in patients with prior EBV infection, research of the association remains plausible [11,[13][14][15].…”
Section: Epidemiology Of Msmentioning
confidence: 90%